Acoustic radiation force impulse elastography of prostate and testes of healthy dogs: preliminary results - Feliciano, M. A. R. [UNESP]; Maronezi, M. C. [UNESP]; Simoes, A. P. R. [UNESP]; Uscategui, R. R. [UNESP]; Maciel, G. S. [UNESP]; Carvalho, C. F.; Canola, J. C. [UNESP]; Vicente, W. R. R. [UNESP] (Wiley-Blackwell, 2015)
Objectives: To describe the use of acoustic radiation force impulse elastography to evaluate the prostate and testes in healthy dogs and establish reference values for these organs. Methods: Thirty dogs were divided into three groups according to their age: juvenile, adult and senior. Echotexture, size, contours and margins of prostate and testes were assessed via ultrasound. The presence of deformities and tissue stiffness (greyscale and homogeneous or heterogeneous) were evaluated by qualitative acoustic radiation force impulse. The shear velocity was evaluated quantitatively. Results: The B mode findings were normal. The qualitative elastography demonstrated that the testes and prostate tissues were hard, homogeneous and not pliable. The shear velocity values were: left testes - juveniles: 128 m/s, adults: 123 m/s and seniors: 123 m/s; right testes - juveniles: 128 m/s, adults: 128 m/s and seniors: 128 m/s; left prostatic lobe - juveniles: 174 m/s, adults: 203 m/s and seniors: 182 m/s; right prostatic lobe - juvenile: 162 m/s, adults: 187 m/s and seniors: 190 m/s with no significant differences between groups.Clinical significance: Acoustic radiation force impulse elastography of the testes and prostate in dogs was easily implemented. This study provides baseline data for these organs.